2016
DOI: 10.1039/c5ra25562g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of chiral nanoparticles based on (pS)- and (pR)-decasubstituted pillar[5]arenes containing secondary amide fragments

Abstract: Employing induced asymmetric synthesis, new decasubstituted pillar[5]arenes containing (R)-(+)- or (S)-(−)-1-phenylethane-1-acetamide fragments have been obtained and characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 40 publications
(82 reference statements)
1
12
0
Order By: Relevance
“…Pillar[n]arenes are capable of anion recognition [12], forming supramolecular complexes [13], and they may serve as components of sensors [14,15]. They form inclusion complexes and associates with aromatic compounds [16], which makes them suitable structure blocks for receptor systems working on the dye-displacement principle for inorganic anions [17] and biologically relevant anion substrates, e.g., adenosine triphosphate [18].…”
Section: Introductionmentioning
confidence: 99%
“…Pillar[n]arenes are capable of anion recognition [12], forming supramolecular complexes [13], and they may serve as components of sensors [14,15]. They form inclusion complexes and associates with aromatic compounds [16], which makes them suitable structure blocks for receptor systems working on the dye-displacement principle for inorganic anions [17] and biologically relevant anion substrates, e.g., adenosine triphosphate [18].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the experimental data obtained by 1 Н NMR spectroscopy unfortunately did not allow us to determine the nature of the interaction by changing the position of the host and guest chemical shifts. The changes that were recorded in the 1 H NMR spectrum of the 3/Ag + system (1:1, 10 −3 M) were related to the broadening of the macrocycle signals, which indirectly indicates the aggregation process and the formation of 3/Ag + associates [34][35][36]. Therefore, we used the 2D 1 H, 1 H-nuclear Overhauser effect spectroscopy (NOESY) NMR methods (Figure 3), 2D 1 H, 1 H-rotational frame nuclear Overhauser effect spectroscopy (ROESY) NMR and 2D diffusion ordered spectroscopy (DOSY) NMR methods to confirm the formation of associates.…”
Section: Synthesis Of Decasubstituted Pillar[5]arenes Containing Sulfmentioning
confidence: 97%
“…Earlier in our research group, [21][22][23][24][25][26] it was shown that the functionalization of the pillar [5]arene with amide fragments increases the solubility of compounds in water and promotes self-association and aggregation of the resulting macrocycles. So, we proposed approach to the introduction of ten amide fragments into the pillar [5]arene structure for the purpose of selective recognition of metal ions, by varying the substituents in the amide fragment (-C(O)-NH-R and -C(O)-NR 2 ).…”
Section: Introductionmentioning
confidence: 96%